2014
DOI: 10.4037/ajcc2014958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lavender Aromatherapy on Vital Signs and Perceived Quality of Sleep in the Intermediate Care Unit: A Pilot Study

Abstract: Background Sleep deprivation in hospitalized patients is common and can have serious detrimental effects on recovery from illness. Lavender aromatherapy has improved sleep in a variety of clinical settings, but the effect has not been tested in the intermediate care unit. Objectives To determine the effect of inhalation of 100% lavender oil on patients’ vital signs and perceived quality of sleep in an intermediate care unit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
70
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 16 publications
(16 reference statements)
0
70
4
2
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] Lavender essential oil was most frequently studied, with results trending toward a positive effect. 20,21,[23][24][25][26][28][29][30][31][33][34][35][36] A small to moderate benefit of lavender on sleep was found in a systematic review of the literature specific to lavender and sleep. 37 Lavender (Lavandula angustifolia) essential oil was selected for the study intervention based on its documented sedative and hypnotic properties 18 and its safety profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] Lavender essential oil was most frequently studied, with results trending toward a positive effect. 20,21,[23][24][25][26][28][29][30][31][33][34][35][36] A small to moderate benefit of lavender on sleep was found in a systematic review of the literature specific to lavender and sleep. 37 Lavender (Lavandula angustifolia) essential oil was selected for the study intervention based on its documented sedative and hypnotic properties 18 and its safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled, their chemical constituents enter the circulatory system through the lungs and the neurochemical pathway via the limbic system. 18 A systematic review of the literature on inhaled essential oils and sleep 19 and 2 additional studies 20,21 identified 17 studies with a wide variety of methodologies. Thirteen of the studies were randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders can be associated with increased sympathetic activity and subsequent increased blood pressure and heart rate, raising the risk for developing cardiovascular problems among patients hospitalized in coronary care units (Hajibagheri et al, 2014). Thus, avoiding sleep disorder in patients with cardiac diseases is also crucial in terms of reducing anxiety (Hajibagheri et al, 2014;Lytle et al, 2014).…”
mentioning
confidence: 99%
“…UDEEF'de hastanın uykusunu etkileyen etmenler yani yatak, ışık, ısı, gürültü gibi çevresel etmenler, hastalığı hakkında yeterli bilgi verilip verilmemesi, kaygı düzeyi gibi psikolojik etmenler ele alınmıştır (23). Literatürde hastanede yatan bireylerin uykusuzluk nedenlerine göz atıldığında; ağrı, gürültü, stres ve kaygı, kalabalık, yatak, yatağın temizlik ve düzeni, ışık gibi faktörlerin önemli olduğu belirlenmiştir (46,47). Hastanede uygulanan rutin işlemler uykunun bölünmesine neden olmakta ya da hastaların alışkın oldukları zaman diliminde uykuya dalmalarını önlemektedir.…”
unclassified
“…Çalışmalar kanser hastalarının ilaç, mod ve ağrıdan dolayı diğer hastalara göre daha kötü uyku kalitesine sahip olduklarını göstermektedir. Akciğer kanseri hastalarda yapılan bir çalışma hastaların %52'sinde uyku bozukluğu, %29'unda ciddi uykusuzluk olduğunu kanıtlamıştır (43,46,48). Bizim çalışmamızda da torakotomi sonrası hastalar ciddi ağrı problemi yaşamaktadırlar ve yakın takip amaçlı yoğun bakım ünitesinde tedavileri yapılmaktadır.…”
unclassified